Traditional food crop marketing in Sub-Saharan Africa: Does gender matter? - Christina Handschuch; Meike Wollni (Georg-August-Universität Göttingen, Courant Research Centre - Poverty, Equity and Growth (CRC-PEG), 2013)
Specialization and commercialization of agricultural production is seen as a key to lift small-scale farmers in developing countries out of poverty. While participation in high-value markets has been shown to be beneficial for farmers, especially the smallest and least endowed farmers are often excluded from these markets due to high transaction costs. In this context, marketing traditional food crops poses an important income alternative. The present study aims to contribute to the scarce literature on traditional food crops by analyzing the factors influencing (a) the households' decision to participate in the finger millet market and (b) the selling prices obtained by the household. A special focus of our analysis lies on the role of gender and collective action. Based on household data from 270 finger millet producers, a probit model on market participation and a linear regression model on the selling price are estimated. Results show that participation in a finger millet group positively influences the decision to market finger millet. While female household members who do not participate in a group are disadvantaged in terms of selling prices, there is no gender effect on selling prices if a female household member participates in a finger millet group.
Keywords: 330; Kenya; finger millet; marketing; collective action; gender